PESANTREN AS A PILLAR OF ISLAMIC CIVILIZATION DEVELOPMENT IN INDONESIA - Hari Nur Azizah; Nicky Estu Putu Muchtar; Freddrick Tiagita Putra (Academicus: Journal of Teaching and Learning, 2023)
This article discusses the role of pesantren as a primary pillar in the development of Islamic civilization in Indonesia. Pesantren is a traditional educational institution that has played a crucial role in shaping and preserving Islamic civilization amidst the changing times. This research aims to analyze the contributions of pesantren in building Islamic civilization and the factors that influence the role of pesantren in the Indonesian context. The research methodology used in this study is literature review, collecting data from various reliable sources such as books, journal articles, and related research reports. In its analysis, this article identifies several key factors that make pesantren a pillar in the development of Islamic civilization in Indonesia. These factors include an educational curriculum based on Islamic values, the role of kyai (religious educators) as spiritual and intellectual leaders, and the social bonds and solidarity within the pesantren community. The results of the study indicate that pesantren plays a significant role in the development of Islamic civilization in Indonesia. Pesantren not only focuses on religious aspects but also provides holistic education involving academic, social, and moral dimensions. Pesantren serves as a place where students, known as santri, can develop their Islamic personalities and gain a deep understanding of Islamic teachings